Nocturnal Melatonin Profiles in Patients with Delayed Sleep-Wake Phase Disorder and Control Sleepers. (October 2015) - Micic, Gorica; Lovato, Nicole; Gradisar, Michael; Burgess, Helen J.; Ferguson, Sally A.; Kennaway, David J.; Lack, Leon
A significant delay in the timing of endogenous circadian rhythms has been associated with delayed sleep phase disorder (DSPD). More recently, other mechanisms have also been proposed to account for this disorder. To further explore the etiology of DSPD, the present study compared nocturnal melatonin profiles of 26 DSPD patients (18 males, 8 females; age, 21.73 ± 4.98 years) and 17 normally timed good sleepers (10 males, 7 females; age, 23.82 ± 5.23 years) in a time-free, dim-light (<10 lux) laboratory environment. A 30-h modified constant routine with alternating 20-min sleep opportunities and 40 min of enforced wakefulness was used to measure the endogenous melatonin circadian rhythm. Salivary melatonin was sampled half-hourly from 1820 h to 0020 h and then hourly from 0120 h to 1620 h. DSPD patients had significantly later timed melatonin profiles that were delayed by approximately 3 h compared to normal sleepers, and there were no notable differences in the relative duration of secretion between groups. However, melatonin secretion between dim-light melatonin onset (DLMO) and acrophase was less prominent in DSPD patients compared to good sleepers, who showed a more acute initial surge of melatonin following the DLMO. Although the regulatory role of melatonin is unknown, abnormal melatonin profiles have been linked to psychiatric and neurological disorders (e.g., major depression, obsessive compulsive disorder, Parkinson disease). These results therefore suggest that in addition to a delayed endogenous circadian rhythm, a diminished initial surge of melatonin secretion following DLMO may contribute to the etiology of DSPD.